1973
DOI: 10.3758/bf03326908
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and retention of avoidance behaviors following septal lesions or scopolamine injections in rats

Abstract: Scopolamine injections and septal lesions were found to have similar behavioral effects on both the acquisition and retention of a two-way avoidance task. However, on a jump-up task, these two manipulations did not have similar effects. Scopolamine impaired the acquisition of a jump-up avoidance such that the animals did not even learn the response, whereas septal lesions resulted in no change in acquisition of this task. Septal lesions prior to retention testing resulted in significantly shorter latencies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Suits and Isaacson (1968) reported striking increases in two-way avoidance responding by rats pretreated with scopolamine (1.0 mg/kg). Similar data have been reported by Worsham and Hamilton (1973) using rats. Oliverio (1968), using mice, found improvements after scopolamine on day 1, but impairments thereafter.…”
Section: Active Avoidancesupporting
confidence: 91%
See 1 more Smart Citation
“…Suits and Isaacson (1968) reported striking increases in two-way avoidance responding by rats pretreated with scopolamine (1.0 mg/kg). Similar data have been reported by Worsham and Hamilton (1973) using rats. Oliverio (1968), using mice, found improvements after scopolamine on day 1, but impairments thereafter.…”
Section: Active Avoidancesupporting
confidence: 91%
“…"Pole jump" avoidance is reduced by scopolamine and l-hyoscamine, but not by methylatropine (Meyers et aI., 1964;Gruber et al, 1967). Almost total elimination of pole jump learning (Worsham and Hamilton, 1973) and impairment of oneway "shuttle box" avoidance learning (Suits and Isaacson, 1968) have also been reported following scopolamine pretreatment (1.0 mg/kg). In contrast, two-way shuttle avoidance responding is usually improved by antagonists.…”
Section: Active Avoidancementioning
confidence: 99%
“…In previous studies (Johnson et al, 1972;Kenyon & Krieckhaus, 1965;Meyer et al, 1970;Schwartzbaum et al, 1967;Worsham & Hamilton, 1973), complete septal lesions have resulted in a facilitated acquisition of an active avoidance response. In the present study, septal lesions caused an increase in avoidance behavior in animals with 1,800 preoperative trials of low avoiding.…”
Section: Discussionmentioning
confidence: 91%
“…A number of studies have investigated the effects of previous avoidance experience on avoidance responding after septal damage. Worsham and Hamilton (1973) showed that rats with 60 trials of preoperative training still exhibited an increase in avoidances for another 60 trials after a septal lesion. Using a leverpress avoidance, Hedges, Van Atta, and Thomas (1975) found that septal lesions facilitated avoidance responding in rats with 1,000 trials of consistent escape responding with avoidance of shock on less than 5% of the trials.…”
mentioning
confidence: 99%
“…In studies on passive avoidance learning in mice it has been consistently shown that scopolamine treatment causes impairment in this type of learning. When the drug has been given during pretraining (acquisition), or post-training (consolidation) sessions, it has been found that scopolamine exerts its deleterious effects primarily during the acquisition phase of learning (Worsham and Hamilton, 1973;Cheal, 1981). In rats scopolamine disrupts spatial learning in the radial arm maze and the Morris water maze (Stevens, 1981;Watts et al, 1981;Sutherland et al, 1982;Whishaw, 1985).…”
Section: Introductionmentioning
confidence: 99%